Intussusception post Clostridium Difficile infection in pediatric patient - Nouf Albalawi; Fawaz Alzahrani; Yousef Alshehri; Ahmed Alolah; Zuhair Mohamed; khalid Sukhi (Elsevier, 2023)
Background: Intussusception is one of the causes of acute abdominal in childhood. Infants can be asymptomatic or symptomatic with a common triad of symptoms abdominal pain, bilious vomiting, and bloody stool. Case presentation: an 8-month-old girl presented to the emergency department with abdominal pain, bilious vomiting, and diarrhea. Diagnosis of intussusception was made based on abdominal imaging, demonstrated bowel within bowel configuration at the right upper abdominal. the patient was managed by fluoroscopy for a reduction. Conclusion: It may be difficult for emergency room doctors to diagnose acute abdominal pain. Anyone under 24 months old who shows acute abdominal pain, bilious vomiting and bloody diarrhea should be suspected of having intussusception. Intussusception should only be treated non-operatively in carefully chosen circumstances. To better understand the factors that cause intussusception after infection, particularly after Clostridium Difficile, more study is required.